2009
DOI: 10.1007/s11695-009-9881-z
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the lower esophageal sphincter and dysmotility of the tubular esophagus in morbidly obese patients

Abstract: Patients with morbid obesity (=BMI>40 kg/m2) have a dysfunction of the LES and an altered esophageal motility, even when they are asymptomatic for GERD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
6
28
0
Order By: Relevance
“…However, recent studies on the relation between obesity and esophageal motility provide conflicting findings. Kuper et al [27] described lower values of LES pressure and esophageal body contraction amplitude in morbidly obese patients compared to non-obese individuals, whereas Schneider and colleagues found higher contraction amplitude in esophageal body of patients with the highest BMI compared to patients with lower BMI [28]. Further studies are needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 93%
“…However, recent studies on the relation between obesity and esophageal motility provide conflicting findings. Kuper et al [27] described lower values of LES pressure and esophageal body contraction amplitude in morbidly obese patients compared to non-obese individuals, whereas Schneider and colleagues found higher contraction amplitude in esophageal body of patients with the highest BMI compared to patients with lower BMI [28]. Further studies are needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 93%
“…However, typical upper gastrointestinal symptoms of GERD, such as heartburn and chest pain, often are absent in these patients. Manometry and pH-metry studies have shown that both symptomatic and asymptomatic morbidly obese individuals have a reduced resting pressure in the lower esophageal sphincter, as well as disturbed esophageal motility, which can lead to an increased incidence of GERD in these patients [25][26][27][28][29]. However, data for macroscopic findings in the upper gastrointestinal tract in morbidly obese patients are still scarce and contradictory regarding both peri-procedure morbidity and rates of pathological findings [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a known risk factor for GERD and/or hiatus hernia (HH) as well as for erosive esophagitis and esophageal adenocarcinoma [2,3]. Approximately 50-70 % of patients undergoing bariatric surgery for morbid obesity have symptomatic reflux, while a concomitant HH is present in 15 % of patients with BMI >35 kg/m 2 [1].…”
Section: Gerd and Obesitymentioning
confidence: 99%
“…This makes the diagnosis and assessment of GERD difficult, particularly when manometry and/or pH metry is not performed as routine [2].…”
Section: Gerd and Obesitymentioning
confidence: 99%